INSTRUMENTS OF SLEEP EVALUATION IN CHILDHOOD: BRAZILIAN LITERATURE'S REVIEW. (Fiep Bulletin - online, 2016)
Introduction: in the child population, the presence of alterations in the sleep pattern is influenced by several factors. They can influence the performance of neuro-psychomotor development and in the quality of life. Objective: to verify the instruments of evaluation of sleep in childhood used in Brazil. Method: we searched studies in the Scielo and Lilacs electronic databases from March to April 2015. The inclusion criteria were the studies published from 2010 and on, in Brazil, in Portuguese and that used instruments of evaluation of sleep in childhood. Results: 621 studies were found initially, however only 07 met all the inclusion criteria, being thus selected. Conclusion: the studies showed the effectiveness of the instruments to analyze and to evaluate sleep disorders in the chil population. It has a low cost, it is easily applied and it is considerably reliable.
Keywords: “sleep”; “questionnaire” and “child”.